1993
DOI: 10.1007/bf01877381
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of long-term prognosis in patients with ovarian cancers by adjuvant sizofiran immunotherapy: a prospective randomized controlled study

Abstract: The effect of immunotherapy using sizofiran (SPG) on the prognosis of patients with ovarian cancers was prospectively studied in a total of 68 patients, who were randomly assigned to either a cisplatin, adriamycin and cyclophosphamide (PAC) therapy group or a PAC plus SPG combination therapy group. The survival rate was significantly higher in patients with stage Ic, II or III cancers treated with the PAC plus SPG combination, compared with the patients treated with PAC alone. In the SPG-receiving patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…For example, it was reported that lentinin was safe and effective for suppressing the adverse events of chemotherapy as well as improving quality of life in patients with advanced colorectal [48 ] and gastric [51 ] cancers. In a randomized controlled trial Schizophyllan (SPG), a b-glucan from Schizophyllan commune, administered in combination with chemotherapy improved the long-term survival rate of patients with ovarian cancer [52]. Similarly, b-glucan from Grifola frondosa combined with chemotherapy decreased the size of lung, liver, and breast tumors in over 60% of patients compared to chemotherapy alone [53].…”
Section: B-glucan and Cancermentioning
confidence: 99%
“…For example, it was reported that lentinin was safe and effective for suppressing the adverse events of chemotherapy as well as improving quality of life in patients with advanced colorectal [48 ] and gastric [51 ] cancers. In a randomized controlled trial Schizophyllan (SPG), a b-glucan from Schizophyllan commune, administered in combination with chemotherapy improved the long-term survival rate of patients with ovarian cancer [52]. Similarly, b-glucan from Grifola frondosa combined with chemotherapy decreased the size of lung, liver, and breast tumors in over 60% of patients compared to chemotherapy alone [53].…”
Section: B-glucan and Cancermentioning
confidence: 99%
“…Sizofirnan (SPG) was administered in all cases. One study (67) was applied to patients at stage IB-IV, and the others were applied to patients at stages II or III (68-72). They compared the survival time, complete remission rate, recurrence, the size of tumor, etc., with positive results being obtained in most cases.…”
Section: Results Of Clinical Experimentsmentioning
confidence: 99%
“…In the study of Masaki Inoue and Yoshiaki Tanaka, 68 ovarian cancer patients were randomly assigned in four groups treated with, respectively, cisplatin, adriamycin, and cyclophosphamide (PAC) or a PAC plus SPG. The results revealed the fact that SPG could activate host immunity which had been damaged by chemotherapy and, as a result, could improve the long-term prognosis (Inoue et al 1993). As to the gastric cancer, SPG seemed to function in the control or elimination of microscopic metastatic foci and/or small-sized macroscopic foci which were present in the stage III patients (Fujimoto et al 1984).…”
Section: Schizophyllanmentioning
confidence: 97%